The Concept of Quality Management for Graduates of the University of Muhammadiyah Prof. Dr. Hamka Based on Maq?sid syar?'ah Jasser Auda Perspective - Rizki Amrillah; Masyitoh Chusnan; N. Oneng Nurul Bariyah (Syntax Corporation Indonesia, 2024)
This study aims to examine the implementation of Maq?sid syar?'ah from Jasser Auda's perspective in quality management of graduates at the University of Muhammadiyah Prof. Dr. Hamka (UHAMKA). Using a qualitative approach, this study integrates the six systemic features of Maq?sid shar?'ah proposed by Jasser Auda(1) (Cognition: Al-Idrakiyah) (2) Wholeness (Wholeness; Al-Kulliyah) (3) Openness; Al-Infitahiyah) (4) (Interrelated-Hierarchy; Al-Harakiriyah Al-Mu'tamadah Tabaduliyan) (5) Multi-dimensionality (Multidimensionality; Ta'addud Al-Ab'ad). While the last one is (6) Purposefulness (Purposefulness; Al-Maqasidiyah) into the quality management framework of higher education graduates. Data was collected through in-depth interviews with various stakeholders as well as analysis of official university documents, including tracer studies. The results of the study show that this Maq?sid shar?'ah-based approach is effective in improving academic competence, soft skills, and spiritual development of UHAMKA graduates. This study concludes that the integration of Maq?sid shar?'ah principles in higher education quality management can produce graduates who are not only academically competent, but also have high moral and spiritual integrity, so that they are ready to compete in the global job market.